2018
DOI: 10.1063/1.5023340
|View full text |Cite
|
Sign up to set email alerts
|

Finite-key analysis for the 1-decoy state QKD protocol

Abstract: It has been shown that in the asymptotic case of infinite-key length, the 2-decoy state QKD protocol outperforms the 1-decoy state protocol. Here, we present a finite-key analysis of the 1-decoy method. Interestingly, we find that for practical block sizes of up to 10 8 bits, the 1-decoy protocol achieves for almost all experimental settings higher secret key rates than the 2-decoy protocol. Since using only one decoy is also easier to implement, we conclude that it is the best choice for QKD, in most common p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
137
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(142 citation statements)
references
References 19 publications
3
137
0
2
Order By: Relevance
“…The intensity modulators are used to carve the pulses and to obtain the two (signal and decoy) intensity levels. We implemented a 1 decoy state protocol, instead of the more common 2 decoy states, because on one side it has been demonstrated that using just 1 decoy does not affect the final system performance (in some cases it even improves them) [34] and on the other side it is easier to implement, in the sense that one intensity modulator driven by a square 2-level signal suffices. The phase modulator is only used for phase randomization, and it can easily be removed from the setup if a phaserandomized pulsed laser is used as source (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity modulators are used to carve the pulses and to obtain the two (signal and decoy) intensity levels. We implemented a 1 decoy state protocol, instead of the more common 2 decoy states, because on one side it has been demonstrated that using just 1 decoy does not affect the final system performance (in some cases it even improves them) [34] and on the other side it is easier to implement, in the sense that one intensity modulator driven by a square 2-level signal suffices. The phase modulator is only used for phase randomization, and it can easily be removed from the setup if a phaserandomized pulsed laser is used as source (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…We chose this specific block size as it corresponds to the overall detection events in the computational basis over a period of 30 seconds, meaning that the acquisition time of our block is exactly 30 seconds. Note that the secret key rate per core shown in Figure 4 a) is obtained only from each core raw key through finite key analysis [34,35,37], meaning that error correction and privacy amplification effects are taken into account but not actually implemented and that the obtained key rates also consider fluctuations given by the finite statistics. These rates show an average of 2.86 Mbit s −1 ± 4.37 kbit s −1 leading to a total multiplexed rate of 105.7 Mbit s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, sec and cor are the secrecy and correctness parameters. Formulas for each of these terms can be found in literature [26]- [29], and are not reported as they are out of the scope of this work. By setting the block size to n Z = 10 9 , and the secrecy and correctness parameters to sec = cor = 10 −15 , provided with our setup channel loss, receiver loss and detectors parameters, the optimal secret key that can be generated is of approximately 5×10 −5 bit/pulse, resulting in a rate of 29.8 kbit/s.…”
Section: Addressing the Stability Problemmentioning
confidence: 99%
“…higher signature rates and longer transmission distance with a simple experimental setup. Firstly, we apply the one-decoy method, which outperforms the two-decoy scheme for almost experimental settings in QKD [27]. More importantly, this method in principle could decrease random number consumptions and experimental complexity in state preparation.…”
Section: Introductionmentioning
confidence: 99%
“…is the binary Shannon entropy function; s L Z,1 and φ U Z,1 denote the lower bound of single-photon counts and the upper bound of single-photon error rate, respectively, which can be estimated with one-decoy shceme [27] in finite-size scenario.…”
Section: Introductionmentioning
confidence: 99%